Uji Reliabilitas Tinetti Asessment Tool Untuk Menilai Keseimbangan Pada Lansia - De Sousa, Auxililiadora, Totok Budi Santoso, S.Fis., S.Pd., M.PH (2016)
BACKGROUND: Balance is body ability for maintance the body. The balance is one of the important components in implementing various activities of daily life. Many clinical tests are currently available to measure the balance in the elderly. Lost of measuring tool to assess the balance that has been proven reliable. However the majority of the instruments for assessing balance for elderly. In reality in everyday life, people are more in need of a dynamic rether than static balance. Regarding the Tinetti Asessment Tool to measure dynamic balance in the few and limited.OBJECTIVE: To determine the reliability of measuring balance in the elderly.METHODS: The study design was observasional decriptive study that prsents the result of measurement of the balance in the elderly as measured by the Tinetti Asessment Tool. Test conducted reliability test. The reliability test by comparing the results of measurements of the Tinetti Asessment Tool at three different raters measuring in the interrater reliability of the result, and by comparing the result of measurements of the Tinetti Asessment Tool on three different occaions as a result of the reliability test intrarater. SUBJECT: Subject were elderly peoplewho appropriate the inclution, exclution, and drop out criteria. Total subjects who appropriate these criteria totaled 31 people. TIME: 1 Mei 2016-20 Mei 2016. PLACE: Society Panti Werdha Dewanata Cilacap and Elderly Flamboyan Society in Purworejo.ANALYSIS: Data were processed with SPSS 17.0 for windows. The reliability test result the reliability analysis scale has Intraclas Corelation Coeffiecient (ICC) of 0,941 for interraterreliability, and amounted to 0,948 for intrarater reliability, which the reliability is good. CONCLUTION: From the analysis it can be concluded that the Tinetti Asessment Tool is reliable for measuring thedynamic balance in the elderly.